EVALUASI PENGELOLAAN KEUANGAN DESA DI DESA SAMBIREJO KABUPATEN LANGKAT - Syahfitri, Hijriah Yana; Nasution, Dito Aditia Darma (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The research approach used in this research is a quantitative approach. This research was conducted in Sambirejo Village, Langkat Regency. The research population includes the Village Head, Village Financial Management Executive (PPKD), Secretary, Head of Head, Kasi, Head of Finance, and the village community. The sample in this research was the Village Head and Head of Finance of Sambirejo Village, Langkat Regency. The data in this research is quantitative data shown in numbers, such as the 2021-2022 APBDesa realization report. Data sources consist of primary and secondary data. Data collection techniques include documentation, literature study, and interviews. The data validity test in this research involves credibility, transferability, dependability and confirmability tests. Data analysis includes data reduction, data display, and conclusion drawing/verification. The research results show that, based on Minister of Home Affairs Regulation no. 20 of 2018, the Sambirejo Village Government has managed village finances in accordance with the principles of transparency, accountability, participation, and budgetary order and discipline, with a high level of effectiveness. This shows that financial management that complies with the provisions can provide benefits to the people of Sambirejo Village.